The experience of suburban modernity : how private transport changed interwar London - Law, Michael John (Studies in popular culture (Manchester, England), 2014)
This title explores how the adoption of new forms of private transport transformed inter-war suburban London. It shows how London's suburban middle classes used their newly found disposable income to enjoy driving, motorcycling and flying. It demonstrates that these new practices were welcomed by many, but met resistance to change from those who were dismayed by the accidents that resulted from increased mobility and the aesthetic and cultural changes that were the consequence of Americanization and suburban development.